Association of interleukin-6 polymorphism (-634C/G) in the promoter region with diabetic nephropathy in type 2 diabetes mellitus (Bangladesh Journal of Medical Science, 2019)
Background:Long term microvascular complications of DM includes: nephropathy, retinopathy, and neuropathy. Increased level of IL-6 and its polymorphism have been associated with diabetic nephropathy.The present study was designed to determine serum level of IL-6 and C/G polymorphism at − 634 position in the promoter region of IL-6 gene in patients with type 2 diabetes mellitus (T2DM) with and without nephropathy.Method: This comparative study was comprised of 164 subjects, divided into two groups of 82 subjects in each. The subjects who had diabetes for more than 5 years without nephropathy were labeled as group-I and the subjects who had diabetes for more than 5 years with nephropathy were labeled as group-II. IL-6 polymorphism was detected by RFLP and its level was determined by ELISA technique. Data was analyzed using SPSS 20.0.Results: In group-I, 14 (17.1%) patients had CC, 47 (57.3%) had CG and 21 (25.6%) had GG polymorphism. In group-II, 9 (11%) patients had CC, 69 (84.1%) had CG and 4 (4.9%) had GG polymorphism. Pearson’s correlation test determined significant association of IL-6 polymorphism (CC,CG,GG) in both the groups (p